Converting brown coal to synthetic liquid fuels through direct coal liquefaction technology: Techno‐economic evaluation. (19th August 2020) - Huang, Ye; Rolfe, Angela; Rezvani, Sina; Herrador, José M. Hidalgo; Franco, Flavio; Pinto, Filomena; Snape, Colin; Hewitt, Neil
Summary: The main objective of this paper is to carry out a techno‐economic evaluation for the direct coal liquefaction (DCL) process based on the two primary conversion options under consideration: (a) catalytic coal liquefaction (CCL) – the use of non‐donor solvents with added hydrogen pressure and (b) thermal coal liquefaction (TCL) – the use of solvents with some H‐donor properties without hydrogen pressure. For this purpose, steady‐state process models for the CCL and TCL are developed. The process modules addresses only the primary DCL process and do not include any upgrading to transport fuels as this will be conducted at refinery facilities. To better understand the process parameters and benefits of each option, detailed simulations have been conducted using the ECLIPSE modelling software. Technical results showed that daily oil yields (light and middle distillates) were around 1208 barrels from the CCL process and 924 barrels from the TCL process when the feed rate of brown coal was 256 t/d (on dry and ash free basis). Based on economic assumptions, the break‐even oil price would be €47.10/barrel with the CCL and €57.81/barrel with the TCL. Abstract : Techno‐economic analysis of two direct coal liquefaction options is evaluated. Catalytic coal liquefaction (CCL) and thermal coal liquefaction (TCL) are considered. CCL consumes more H2 but produces less heavy oil products than TCL. Oil yields from CCL are 1208 and TCL 924 barrels per day when daily coal feed was 256 t. Break‐even oil price for CCL is €47.10/barrel and TCL €57.81/barrel.